Fungal Screening and Isolation of Cellulolytic, Mannan and Protein Degrading Enzyme Producers in Palm Kernel Cake Solid State Fermentation - Farida Asras, Mohd Fazli (2009)
Palm Kernel Cake (PKC), an agro-industrial by-product obtained after extraction of oil palm from oil palm seeds is used extensively in the animal feed industry but has limited used in poultry feed due to its high fiber and low protein contents. In this study, PKC was used as a substrate in solid state fermentation (SSF) by locally-isolated strains and their feasibility for cellulase and mannanase enzymes production were investigated. The potential isolates were obtained from various sources such as peat soil, rotten rice chaff, ‘Tanah Bakar’, rotten palm frond and raw PKC. The isolates were screened based on the clearing zone method and on selective agar media containing substrates such as locust bean gum (LBG), carboxymethylcellulose (CMC), potato dextrose, mannan and PKC. Forty-eight fungal cultures have been screened and isolated based on the selective agars. Only thirty-one isolates were able to grow well after multi-subculturing techniques. The microbial activities of the isolates were accessed through clearing zone by chromogenic substrates such as Azo-carob galactomannan and Azo-CM cellulose. The diameter of clearing zone on the agar plate was observed every 24 h until 120 h. Cultivation of the strains was carried out at 50% moisture content using shake flask and pre-germinated spores were preferred as the inoculum. The effects of cultivation conditions such as moisture level, inoculum concentration and agitation were investigated with the aim to achieve maximum production of cellulase and mannanase enzymes. Shaking at 120 rpm was found as the best agitation speed in the pre-germination process to be used as the inoculum. The samples were analyzed for neutral detergent fiber, acid detergent fiber, crude fiber and crude protein using Near Infrared Reflectance Spectroscopy analysis. The best enzymes producer was fungal isolate D1 with specific enzyme exoglucanase activity of 17.9323 U/mg, specific enzyme endoglucanase activity of 41.6008 U/mg and specific enzyme β–glucosidase activity of 79.2626 U/mg using the pre-optimized conditions on the fifth day of fermentation process. About 50.1036 U/mg of specific enzyme mannanase activity was achieved on the fourth day of fermentation process using PKC as the substrate. The fibre degradation increased significantly. Neutral and acid detergent fibers were reduced from 85.16 to 21.72% on the sixth day and 45.18 to 17.18% at eighth day of fermentation process, respectively. The protein content increased from 13.31 to 31.53% on the eighth day. Lower cellulase and mannanase enzymes activities were obtained in other isolates. The highest cellulolytic and mannan-degrading enzymes producer was identified using microscopic. Under the microscopic view, isolate D1 was identified as Aspergillus sp. The identity of the isolate was further confirmed and belongs to Aspergillus sp. after observation under Scanning Electron Microscope (SEM). As a result, isolate D1 was identified as Aspergillus sp.